MANUFACTURE OF PLASTICS FILM CONTAINING OF POLYSTIRENE, POLYCAPROLACTONE, POLY(3-HIDROKSIBUTYRATE-CO-3- HIDROXYVALERATE) AND BIODEGRADATION STUDY IN OCEAN WATER - Asiska Permata Dewi; Erizal Zaini; Akmal Djamaan (Jurnal Riset Kimia, 2014)
Â ABSTRACTThe manufacture of a biodegradable plastics film containing of polymer synthetic polystyrene(PS) and biopolymer of polycaprolactone (PCL), poly(3-hydroxybutyrate-co-3-hydroxyvalerate)[P(3HB-ko-3HV)] and biodegradation study in ocean water has been carried out. Plastics filmcontaining of PS/PCL/P(3HB-ko-3HV) produced by blending techniques followed by solventcasting with ratios were of 100/0/0, 95/5/0, 95/0/5, 90/5/5, 85/10/5, 85/5/10. This testing wasconducted based on immersion test method recommend by American Society for Testing andMaterials. Poly blend plastics film PS/PCL/P(3HB-ko-3HV) were characterized by tensilestrength, thermal properties and SEM analysis. The profiles of the rate biodegradation view byweight reduction of the tested plastic film for 1-7 weeks period. Tensile strength analysisshowed the decreasing of tensile strength with the addition of P(3HB-ko-3HV). Thermalanalysis showed a decreasing in the melting point with the addition of PCL and P(3HB-co-3HV). SEM micrograph showed the destruction occurred and erosion at surface of plastic filmduring observation time. The rate of biodegradation showed that increasing of PCL and P (3HBco-3HV) in a mixture of plastic film, so biodegradation increased.Keywords: polystyrene, polycaprolactone, poly(3-hidroxybutyrate-co-3-hydroxyvalerate),biodegradation, film plastic.